Penulisan Skenario Program Cerita Lepas “Kopi Hitam Tanpa Gula” dengan Penataan Ketepatan Point of Attack dalam Skenario - Diah Romdaniah (Saraswati)
Women in the third person in a romantic relationship becomes the object creation in this artwork. This work aims to reveal the strongest side of a woman to defend themselves in life. Female figure who is able to live independently and tough in her life will be realized in the form of a scenario entitled "Kopi Hitam Tanpa Gula" with the concept of the arrangement in a accuracy point of attack scenarios. Point of Attack intended to allow the audience to know as soon as possible motives of the main character perform an action to resolve the problem.Creation process uses structure 3 innings as part of dramatic storytelling. This artwork using the symbol as a messenger in the scenario. Symbols used have the meaning in every gesture, played by the main character in the scenario. Each symbol will be placed in each half. Coffee as a form of manifestation of any experienced development phase of a major figure in his life is the main symbol of which is the explanation of the meaning of the story implied. The position of coffee as a symbol inserted in some scenes is one way to make the audience how to the coffee simbol is related to the life of the main character and is closely related to other figures that are directly related to the main character of story.Keywords: women, scenarios, point of attack, the symbol of coffee.